Structural robustness of combat networks of weapon system-of-systems based on the operation loop. Issue 3 (17th February 2017) - Li, Jichao; Tan, Yuejin; Yang, Kewei; Zhang, Xiaoke; Ge, Bingfeng
ABSTRACT: The structural robustness of the combat network of weapon system-of-systems (CNWSOS) has been widely used to characterise its operation ability and survivability in the integrated joint operations. In this paper, after introducing the concept of the operation loop, a directed CNWSOS network model is first put forward. Then, the directed natural connectivity, a new measure of the CNWSOS robustness that extends the concept of natural connectivity to the directed combat networks, is proposed to provide both a definite physical meaning and a simple mathematical formulation. Last, the feasibility and effectiveness of the proposed structural robustness measure are demonstrated using both numerical experiments and an empirical case study. The directed natural connectivity facilitates a more sensitive and precise quantitative analysis of the structural robustness, which in turn provides useful insights for designing a more robust CNWSOS, including improving the accuracy of intelligence acquisition, enhancing the communication capabilities of weapon systems, and strengthening the capability of precision strikes.